2020
DOI: 10.4187/respcare.08145
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Insufflation-Exsufflation With Oscillations in Amyotrophic Lateral Sclerosis With Home Ventilation via Tracheostomy

Abstract: BACKGROUND: Mechanical insufflation-exsufflation (MI-E) applied via tracheostomy tubes in patients with amyotrophic lateral sclerosis (ALS) who are on home mechanical ventilation via tracheostomy is an effective procedure for respiratory secretion management. Nonetheless, tenacious secretions may remain and increase the risk of respiratory infections. The aim of this study was to determine whether adding oscillations to MI-E could reduce the rate of respiratory infections and the need for bronchoscopy to remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Manufactures may highlight MI-E with the addition of oscillations as being a potential substitute for using HFCWO. Sancho and co-workers [ 66 , 67 , 68 ] report their work looking at the effect of the addition of oscillations on MI-E. In their studies, they used an insufflation pressure of around +40 cm H 2 O and an exsufflation pressure of −40 cm H 2 O, insufflation time 2 s and exsufflation time 3 s. Oscillations were applied with a frequency of 15 Hz with an amplitude of 10 cm H 2 O, usually for two sessions of 6–8 cycles applied each day and additionally when necessary.…”
Section: Mi-e With the Addition Of Oscillationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manufactures may highlight MI-E with the addition of oscillations as being a potential substitute for using HFCWO. Sancho and co-workers [ 66 , 67 , 68 ] report their work looking at the effect of the addition of oscillations on MI-E. In their studies, they used an insufflation pressure of around +40 cm H 2 O and an exsufflation pressure of −40 cm H 2 O, insufflation time 2 s and exsufflation time 3 s. Oscillations were applied with a frequency of 15 Hz with an amplitude of 10 cm H 2 O, usually for two sessions of 6–8 cycles applied each day and additionally when necessary.…”
Section: Mi-e With the Addition Of Oscillationsmentioning
confidence: 99%
“…Long-term use (1 year) in non-invasively managed and tracheostomized ALS patients, who use MI-E compared to MI-E with oscillations, showed no benefit. They found no decrease in hospitalizations or increase in survival in either group [ 66 , 67 ], and MI-E with oscillations did not reduce the need to perform invasive procedures for mucus removal or decrease the risk of respiratory tract infections nor improve 1-year survival compared to MI-E alone [ 66 , 67 ]. It would make sense that MI-E with the addition of oscillations may help to move secretions.…”
Section: Mi-e With the Addition Of Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Cost, the need for caregiver assistance, and subsequent use of proximal airway clearance techniques have led to the conditional recommendation, as a result of very low certainty of the evidence, in the most recent clinical practice guideline related to the respiratory management of patients with neuromuscular weakness. 67 Due to logistical and reimbursement issues related to obtaining multiple airway clearance devices, Sancho et al [68][69][70] have performed a series of studies on the addition of highfrequency oscillations with MI-E. Though theoretically, the addition of in-line oscillations could have a direct effect on outcomes of patients with ALS, studies thus far have not shown statistical significance in the realms of enhanced cough peak flow, a reduction in the need to perform invasive secretion management procedures, or a decreased risk of respiratory infections and hospital admissions in those on home ventilation with a tracheostomy.…”
Section: Sputum Mobilizationmentioning
confidence: 99%